Integrated interpretation of magnetotelluric and potential field data: assessing the northeast Kimberley region. Issue 1 (1st December 2016) - Lindsay, Mark; Spratt, Jessica; Aitken, Alan; Dentith, Mike; Occhipinti, Sandra; Metelka, Vaclav; Hollis, Julie; Tyler, Ian
Abstract : An integrated interpretation of potential field and magnetotelluric (MT) data was performed in the east Kimberley, northern Western Australia Structural interpretation of potential field data was constrained by geological field observations, petrophysics, remote-sensing and an understanding of the tectonic history of the region. Forward modelling of the potential field data located along the same survey traverse as the magnetotelluric data allowed comparison between the two datasets to assess complementarity of images and assist interpretation. Interpreted features include the presence of large-scale structures and associated electrical anomalies that indicate the presence of mineralisation deep in the crust, and guide prediction of mineralisation at or near the surface. The King River Fault is revealed to be a crustal-scale, west-dipping structure, which footwall bounds the western side of a large resistive body. A conductive anomaly is also located on the hanging wall of the King River Fault. A number of scenarios are discussed to the source of conductivity, including the presence of sulphides, saline water and graphite. Our assessment suggests that graphitic rocks, most likely with some sulphide content, contribute to the strength of this anomaly, and highlights the known potential of the east Kimberley to host graphite deposits. The conductive anomaly has a spatial and geometric correlation to Speewah Dome, a known prospective region. The depth of the conductor (c. 5km) precludes mining, but does indicate King River Fault is likely to form a mineralising conduit, and may contribute to possible Pb-Zn mineralisation where the fault reaches the surface.